H-Amalgamation Property in the Class of Torsion Free Abelian Groups (Contemporary Mathematics, 2025)
It is proved that the classes of torsion free abelian groups and divisible torsion free abelian groups have unique positive existentially closed model up to isomorphism. we give complete description of h-amalgamation bases in the class of non-trivial torsion free abelian groups.
Keywords: Positive logic; h-inductive theory; Amalgamation; Existentially closed